Baseline cytokine profiling identifies novel risk factors for invasive fungal disease among haematology patients undergoing intensive chemotherapy or haematopoietic stem cell transplantation. Issue 3 (September 2016) - Ceesay, M. Mansour; Kordasti, Shahram; Rufaie, Eamaan; Lea, Nicholas; Smith, Melvyn; Wade, Jim; Douiri, Abdel; Mufti, Ghulam J.; Pagliuca, Antonio
Summary: Background: Invasive fungal disease (IFD) is a disease of immunocompromised hosts. Cytokines are important mediators of innate and adaptive immune system. The aim of this study was to identify cytokine profiles that correlate with increased risk of IFD. Methods: We prospectively enrolled 172 adult haematology patients undergoing intensive chemotherapy, immunosuppressive therapy, and haematopoietic stem cell transplantation. Pro-inflammatory cytokine profiling using 30-plex Luminex assay was performed at baseline and during treatment. Nine single nucleotide polymorphisms (TLR1, TLR2, TLR3, TLR4.1, TLR4.2, TLR6, CLEC7A, CARD9, and INFG) were investigated among transplant recipients and donors. Findings: The incidence of IFD in this cohort was 16.9% (29/172). Median baseline serum concentrations of IL-15, IL-2R, CCL2, and MIP-1α were significantly higher whilst IL-4 was lower in patients with proven/probable IFD compared to those with no evidence of IFD. Baseline high IL-2R and CCL2 were associated with increased risk of IFD in the multivariate analysis (adjusted hazard ratio 2.3 [95% CI 1.1–5.1; P = 0.037], and hazard ratio 2.7 [95% CI 1.2–6.1; P = 0.016], respectively). However, these differences were not significant in follow up measurements. Similarly, no significant independent prognostic value was associated with baseline cytokine profile. Interpretation: High baseline IL-2R and CCL2 concentrations were independent indicators of the risk of developing IFD and could be used to identify patients for enhanced prophylaxis and early antifungal therapy. Highlights: Baseline cytokine profile provide significant insight into the immunological milieu prior to immunosuppressive therapy. Baseline IL2R and CCL2 are independent indicators of risk of developing IFD. Follow-up cytokine profile may not provide any additional value in IFD risk.